THE HIGH INTENSITY INTERVAL TRAINING (HIIT) CORRELATES WITH TELOMERE LENGTH - Sherla Wijoyo; Debby Chesilya Wijaya; Lisye Marrilyn Lukas; I Putu Gede Adiatmika (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
There are many types of training for exercise in this current era where personalized workout is very popular nowadays. One of the popular workout regimens is the high intensity interval training where it only took half a time than a normal workout time, which may encourage people to exercise more. Recent studies had shown that exercise influence biological aging process, one of the markers is telomere length. One of the characteristics of cellular aging is telomere shortening, where the telomeres shorten as people age. There are many factors that may hasten or slow down this process, which is oxidative stress, lifestyle, chronic inflammation, stress, chronic diseases, and exercises. The primary goal of this literature review is to analyze and investigate the correlation between high intensity interval training (HIIT) and telomere length. The approach taken for this review is from multiple journals using many searches engine like Google Scholar, PubMed, Science Direct and Mendeley Search. The results for each article were reviewed and compared to determine the correlation between high intensity interval training with telomere length. The conclusion of this study showed that people who exercise with high intensity interval training have a considerable lengthening of telomeres.